The Era of Technique and Modes of Existence in the Contemporary (Phenomenology, Humanities and Sciences, 2022)
In order to clarify the main determinations of our historical horizon and how they appear in the ways of being of contemporary man, we conducted bibliographic research in a Narrative Review of Literature. Following Heidegger's phenomenology-hermeneutics, mainly in his text The question concerning technology, we followed our path in the attempt of a more originary apprehension of the senses that underlie our historical horizon. Considering Bauman’s thoughts, in Liquid Modernity, and Duarte's analysis of Lives at Risk, we propose to characterize the contemporary era and to discover other possibilities for understanding it, taking into account the modes of being of man in the daily life of this Era of technique. We intend, therefore, to list elements to make it possible for a psychological investigation to approach social issues based on the historically constituted articulations in the man-world relationship, overcoming the existing dichotomies between a psychic interiority and social exteriority.
Keywords: Social psychology; Contemporary; Heidegger; Bauman; Modernity